2022
DOI: 10.1039/d2qo00698g
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the application of ylide-like species in [4 + 1]-annulation reactions: an updated review

Abstract: In this review, advances in [4+1]‐annulation reactions involving sulfonium, sulfoxonium and ammonium ylides, as well as diazo compounds and carbenes are summarized over the last 6 years. Newly emerged methods...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 143 publications
0
13
0
Order By: Relevance
“…Being highly active Michael acceptors, azoalkenes react with nucleophiles (Grignard reagents, enolates, amines, silyl azides, ylides, etc.) to give α-substituted hydrazones ( Attanasi and Caglioti, 1986 ; Schantl, 1996 ; Attanasi et al, 2002 ; Attanasi et al, 2009 ; Lemos, 2009 ; Lopes et al, 2018 ; Ushakov et al, 2022 ). Surprisingly, the addition of P -nucleophiles to azoalkenes remains underexplored ( Attanasi et al, 1992 ; Attanasi et al, 2005 ; Attanasi et al, 2008 ), and no examples of the addition of disubstituted phosphine oxides R 2 P(O)H have been reported to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Being highly active Michael acceptors, azoalkenes react with nucleophiles (Grignard reagents, enolates, amines, silyl azides, ylides, etc.) to give α-substituted hydrazones ( Attanasi and Caglioti, 1986 ; Schantl, 1996 ; Attanasi et al, 2002 ; Attanasi et al, 2009 ; Lemos, 2009 ; Lopes et al, 2018 ; Ushakov et al, 2022 ). Surprisingly, the addition of P -nucleophiles to azoalkenes remains underexplored ( Attanasi et al, 1992 ; Attanasi et al, 2005 ; Attanasi et al, 2008 ), and no examples of the addition of disubstituted phosphine oxides R 2 P(O)H have been reported to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…However, among the diverse prominent organosulfur reagents, sulfur-based ylides should belong to the most important and widely-used sulfurcontaining reactants in the realm of organic synthetic chemistry. Through literature survey and search, it was found that since the pioneering work of Ingold and Jessop [9] and the groundbreaking work of Johnson and Lacount [10] , Corey and Chaykovsky in the 1960s [11][12][13][14] , the study on sulfur-based ylides chemistry has achieved an impressive development during the past nearly 60 years [15][16][17][18][19] . In this area, especially, stabilized sulfonium and sulfoxonium ylides bearing a carbonyl group at the α-carbon atom [Figure 1] have occupied a dominant position, probably due to some of their inherent characteristics including thermal stability, easy preparation and use, and low toxicity, as well as owing to their powerful functions as nucleophilic 1,1'dipolar species for realizing numerous chemical transformations.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we wish to report the results of our investigation aimed toward the construction of 2,3-furan-fused heterocycles based on a formal cycloisomerization/[4 + 1] cycloaddition 8 reaction sequence of enyne-amides with sulfur ylides 9 (Scheme 1c). To our surprise, the reaction employing an α-keto sulfur ylide did not afford the expected furan-fused dihydropyrrole product but instead gave an α-pyrone, whose structure was determined by single-crystal X-ray diffraction analysis (see the ESI†).…”
mentioning
confidence: 99%